Cytotoxicity of Various Endodontic Materials on Stem Cells of Human Apical Papilla - Saberi, Eshagh Ali; Karkehabadi, Hamed; Farhad Mollashahi, Narges (Iranian Endodontic Journal, 2016)
Introduction: This in vitro study assessed and compared the cytotoxicity of mineral trioxide aggregate (MTA), calcium-enriched mixture (CEM) cement, Biodentine (BD) and octacalcium phosphate (OCP) on stem cells of the human apical papilla (SCAP). Methods and Materials: SCAPs were isolated from two semi-impacted third molars. The cells were cultured in wells of an insert 24-well plate and were then incubated. The plates were then removed from the incubator and randomly divided into four experimental groups that were exposed to 1-mm discs of set MTA, CEM, BD or OCP, and one untreated control group. After 24, 48 and 168 h, the plates were removed from the incubator and 3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyl tetrazolium bromide (MTT) solution was added to each well. Data were analyzed at different time points using the repeated measures ANOVA followed by Bonferroni test and the level of significance was set at 0.05. Results: Cytotoxicity of the four materials was not significantly different from that of the control group at 24, 48 and 168 h (P>0.05). Two-by-two comparison revealed that cytotoxicity of MTA and CEM cement was significantly different from each other at 168 h (P<0.05) although the cytotoxicity of CEM was less than MTA. Cytotoxicity of OCP and MTA was also significantly different from each other at 48 h and OCP had more favorable biocompatibility than MTA (P<0.05). Conclusion: CEM, OCP, BD and MTA showed acceptable biocompatibility when exposed to SCAP. Over time, CEM showed the least cytotoxicity among the materials under study. Keywords: Biodentine; Calcium-Enriched Mixture; Cytotoxicity; Endodontic Biomaterials; Mineral Trioxide Aggregate; MTT Assay; Stem Cells of Apical Papilla